-
Notifications
You must be signed in to change notification settings - Fork 7
New issue
Have a question about this project? Sign up for a free GitHub account to open an issue and contact its maintainers and the community.
By clicking “Sign up for GitHub”, you agree to our terms of service and privacy statement. We’ll occasionally send you account related emails.
Already on GitHub? Sign in to your account
Changing the Equation #1
Comments
According to your error, it seems you have a type mismatch. Try to force
I'm not sure, but it should do the trick. |
I'm sorry for the delay, it's have been a busy week. |
Can you share your experiments? I tried to reproduce it based on the shared code but didn't get much success. |
I apologize for the delayed response. Thank you for looking into this. Not much of a change in the other two experiments. In case 1: In case 2: c1 = 1
c2 = 0.5
# Implementing mask c = c1 * (x>0.5) + c2 *(x<=0.5)
c_s = tf.where(x[:, 0:1] <= 0.5, x[:, 0:1] *0 + c1, x[:, 0:1] * 0 + c2)
f_u = u_tt - (c_s ** 2) * u_xx Please let me know if you're able to reproduce the problem. |
Hello, and thank you for the fantastic framework!
I tried changing plugging in a different equation:
f_u = u_tt - (c**2) * u_xx
with IC:
u(x,0) = 0
and BC:
u(0,t) = sin(4 * pi * freq * t)
u(1,t) = 0
The following is my code implementation:
I encountered what seems like a simple error, but I cannot resolve it. The error script is:
Any ideas?
The text was updated successfully, but these errors were encountered: